The influence of shelf-level product presentations on Product and category perceptions. a study of visual merchandising using a data driven approach - V, Gopakumar; S, Sandheep (International Journal of Engineering and Technology, 2018)
Indiaâ€™s growing Retail Industry has been widely acknowledged one of the most lucrative in the whole world. It captures the wide spectrum from very large malls, specialty stores, big-box discount stores to the smallest kirana (neighborhood) stores. Modern and organized retailers use various visual merchandising techniques to attract attention, elicit consideration, influence purchase decisions and retain customers. This study aims to understand the impact of various Visual Merchandising presentation techniques on consumerâ€™s perception of the product attributes and perception of the retail outlet using data generated out of experiments conducted using the aid of advanced applications of IT. An online survey was conducted among 107 respondents across 35 Indian cities, with standard scales to measure the factors considered in the study. ANOVA performed using STATA MP software, on the data indicates that consumers perceived that vertical and horizontal product presentation offered better variety and presentation compared to an unordered presentation. No difference between the impact of vertical and horizontal product presentation were found. Retail stores can better manage perception about the product attributes and their store among customers by choosing the ordered merchandising style for product presentation.Â Â